1990
DOI: 10.1111/j.1476-5381.1990.tb14140.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cocaine on intracellular Ca2+ handling and myofilament Ca2+ responsiveness of ferret ventricular myocardium

Abstract: 1 When ferret right ventricular papillary muscles were stimulated with threshold punctate pulses (0.33 Hz; 30'C), cocaine, 10-M, increased peak tension development from 815 + 120 to 1125 ± 180mg (P < 0.05) and increased the rate of relaxation from peak tension (time to 80% decline from peak tension decreased from 155 + 11 to 144 + 11 ms; P < 0.05). These changes in the twitch were associated with comparable changes in the amplitude and time course of the calcium transient measured with aequorin (amplitude incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…The present study represents the first direct evidence that cocaine and cocaethylene can alter the Ca2+-dependent steps of excitation-contraction coupling in adult mammalian cardiomyocytes. We previously reported that cocaine produced positive inotropic effects at concentrations of 106 to 10-5M, and negative inotropic effects only at concentrations > 1 x 10-4 M in ferret papillary muscles with intact nerve endings (Perreault et al, 1990). In the present study, we found negative inotropic actions on single myocytes over the entire effective dose-range, indicating that the direct action of cocaine on myocardial cells is to decrease contractility.…”
Section: Discussionsupporting
confidence: 57%
“…The present study represents the first direct evidence that cocaine and cocaethylene can alter the Ca2+-dependent steps of excitation-contraction coupling in adult mammalian cardiomyocytes. We previously reported that cocaine produced positive inotropic effects at concentrations of 106 to 10-5M, and negative inotropic effects only at concentrations > 1 x 10-4 M in ferret papillary muscles with intact nerve endings (Perreault et al, 1990). In the present study, we found negative inotropic actions on single myocytes over the entire effective dose-range, indicating that the direct action of cocaine on myocardial cells is to decrease contractility.…”
Section: Discussionsupporting
confidence: 57%
“…This in turn leads to prolongation of the calcium current and a negative lusitropic effect. 45 The present study has several potential limitations. No data were collected on the method of cocaine exposure, for example, intravenous, intranasal, or inhaled crack cocaine use.…”
Section: Discussionmentioning
confidence: 94%
“…A possible mechanism for these effects is that cocaine may alter Ca 2ϩ handling by myocytes. For example, Perreault et al 45 demonstrated that cocaine can cause an increase in cytosolic Ca 2ϩ concentration in isolated myocardial tissue. This in turn leads to prolongation of the calcium current and a negative lusitropic effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely, but possible, that this action of the drug could have produced myocardial depression in conjunction with the other anaesthetics utilized in the Yorkshire swine. However, such effects are usually expected in concentrations greater that l0-5 M, which would not have been exceeded except at the higher doses in our experiments (Perreault et al, 1990).…”
Section: Systemic Haemodynamicsmentioning
confidence: 97%